NON-PERFORMING LOANS AND PROFITABILITY OF PRIMARY MORTGAGE BANKS IN NIGERIA 2012-2023 (Journal of the Management Sciences, 2024)
This study examined the effect of non-performing loans (NPL) on the profitability of primary mortgage banks in Nigeria from 2012 to 2023. Utilizing time series data from the Nigeria Deposit Insurance Corporation's annual report for 2023, the research investigated how variables such as NPL, capital adequacy ratio (CAR), and loan-to-deposit ratio (LDR) influence return on assets (ROA). Auto-regressive distributed lag models (ARDL) were applied for the analysis, revealing that while non-performing loans had a negative effect, this effect was statistically insignificant over the study period. The study suggests that primary mortgage banks should focus on enhancing credit risk management, optimizing loan recovery strategies, diversifying their loan portfolios, improving capital adequacy, ensuring regulatory compliance, and investing in technology and data analytics to strengthen their operational and financial resilience.
Keywords: Non-Performing loans and profitability of primary mortgage banks in Nigeria.